2019
DOI: 10.1111/mice.12458
|View full text |Cite
|
Sign up to set email alerts
|

Deep leaf‐bootstrapping generative adversarial network for structural image data augmentation

Abstract: Employing Deep Learning (DL) technologies to solve Civil Engineering problems is an emerging topic in recent years. However, due to the lack of labeled data, it is difficult to obtain accurate results with DL. One commonly used method to tackle this issue is to use affine transformation to augment the data set, but it can only generate new images that are highly correlated with the original ones. Moreover, unlike normal natural objects, distribution of structural images is much more complex and mixed. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 25 publications
3
89
0
Order By: Relevance
“…At present, deep learning methods are popularly applied for various applications. For example, damage identification on structures with images (Cha, Choi, & Büyüköztürk, 2017;Gao, Kong, & Mosalam, 2019;Gao & Mosalam, 2018;Li, Zhao, & Zhou, 2019;Ni, Zhang, & Chen, 2019;Wu et al, 2019;Yang et al, 2018), with sensor measurements (Huang, Beck, & Li, 2019;Y. Zhang, Miyamori, Mikami, & Saito, 2019), concrete property estimation (Rafiei, Khushefati, Demirboga, & Adeli, 2017), and vehicle type detection in real traffic data (Molina-Cabello, Luque-Baena, López-Rubio, & Thurnhofer-Hemsi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At present, deep learning methods are popularly applied for various applications. For example, damage identification on structures with images (Cha, Choi, & Büyüköztürk, 2017;Gao, Kong, & Mosalam, 2019;Gao & Mosalam, 2018;Li, Zhao, & Zhou, 2019;Ni, Zhang, & Chen, 2019;Wu et al, 2019;Yang et al, 2018), with sensor measurements (Huang, Beck, & Li, 2019;Y. Zhang, Miyamori, Mikami, & Saito, 2019), concrete property estimation (Rafiei, Khushefati, Demirboga, & Adeli, 2017), and vehicle type detection in real traffic data (Molina-Cabello, Luque-Baena, López-Rubio, & Thurnhofer-Hemsi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The experience with CACAIE during the review process of (Gao & Mosalam, 2018) was not an exception or an anomaly. This became evident as we experienced the same willingness to accept transdisciplinary research with expeditious and rigorous review process during our second submission, recently published as Gao, Kong, and Mosalam (2019).…”
Section: Expediency and Rigormentioning
confidence: 80%
“…Recently, some studies have demonstrated that generative adversarial networks (GANs) are well suited for EEG-DA [25,40,41]. However, few studies were conducted on the analysis of MI signals.…”
Section: Electroencephalogram (Eeg) Pattern Augmentation Methods Limimentioning
confidence: 99%